PENYESUAIAN DIRI MENJADI âSINGLE PARENTâ (Studi Kasus: Terhadap Janda Di Nagari Abai Siat Kecamatan Koto Besar Kabupaten Dharmasraya) - Anggraini, Yuliza - (Pendidikan Sosiologi, 2014)
If we seen in Nagari Abai Siat, District Koto Besar, Dharmasraya, where many heads of households headed by women, the number of household heads until in March 2014, households headed by women are 32 kk become single parents due to divorce. To the effectof observational identifies and description is single parent in Nagari Abai Siat, District Koto Besar, Dharmasraya. This type of the research is descriptive qualitative research. Collecting data with non-participant observation and in-depth interviews and documentary studies. The analysis used is the data analysis Miles and Huberman. The results showed that the changes that occur after a divorce is, among others, (1) changes in subsistence (2) changes in working time (3) changes in feed that protection. Forms of adjustment itself as a "single parent" is to (1) work, (2) look for a second job, (3) requesting assistance extended family and friends (4) divide the household chores for children.